2012
DOI: 10.4067/s0718-95162012000200006
|View full text |Cite
|
Sign up to set email alerts
|

The reduction in proline buildup in mycorrhizal plants affected by nematodes

Abstract: Plants stressed by pathogens activate a variety of defense mechanisms to survive. The osmoprotector amino acids, including proline, are among these defense mechanisms. In this work, the effects of arbuscular mycorrhizal fungi on plants infested by root-knot nematodes were evaluated with regard to the accumulation of the osmoprotectant proline. A 2x3 factorial design was established with 8 treatmentswith and without nematodes, with and without mycorrhizae, and with and without fertilizer application -with 4 rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
(31 reference statements)
1
2
0
1
Order By: Relevance
“…As a result, plants colonized by AMF with a lower proline accumulation would be less harmed under WD and thus more successfully in avoidance of WD [1] . Similar results were found in the Impatiens balsamina plants infected by nematodes ( Meloidogyne incognita ) and a mixture of eight AMF species [36] . Therefore, the AM plants might not need to synthetize more proline to tolerate soil water deficit.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As a result, plants colonized by AMF with a lower proline accumulation would be less harmed under WD and thus more successfully in avoidance of WD [1] . Similar results were found in the Impatiens balsamina plants infected by nematodes ( Meloidogyne incognita ) and a mixture of eight AMF species [36] . Therefore, the AM plants might not need to synthetize more proline to tolerate soil water deficit.…”
Section: Discussionsupporting
confidence: 81%
“…Augé and Moore [21] proposed that lower proline accumulation in AM plants was attributed to less injury by WD. It seems that proline accumulation may act as an appropriate indicator to evaluate the AM functioning on drought tolerance of host plants [22] . Further studies are thus needed to understand these discrepancies if a net proline accumulation relates to the activity of proline synthetases and/or catabolic enzymes in AM plants under WD.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kyriacou and Rouphael [32], tomatoes are a rich source of minerals. In a study by Banuelos et al [33], mycorrhizal inoculation of tomato and carrot plants increased their resistance to nematodes, and the weight of mycorrhizal plants was higher than that of non-mycorrhizal control plants. Schroeder and Janos [34] reported that at low P availability, root inoculation with mycorrhizal fungi had a beneficial influence on DM accumulation in tomato plants and cilantro.…”
Section: Resultsmentioning
confidence: 94%
“…Las cepas utilizadas son nativas de la región, el consorcio de HMA ya había sido probado y demostrado su eficiencia en otros cultivos (Ferrera et al, 2007;Sangabriel-Conde et al, 2010;Bañuelos et al, 2012;Zulueta-Rodríguez et al, 2013;Bañuelos et al, 2014). Por su parte, las cepas A. niger, P. brevicompactum y P. waksmanii también son nativas de la región centro de Veracruz, ya se había demostrado su capacidad como solubilizadoras de fosfato de calcio en condiciones in vitro (Perea, 2019).…”
Section: Variables De Crecimiento De Las Plantasunclassified